Расчетно-экспериментальное уточнение параметров численных моделей элементов "выбивная машина - технологическая нагрузка" - Барчан, Евгений Николаевич; Полищук, Т. Р.; Грабовский, Андрей Владимирович (Национальный технический университет "Харьковский политехнический институт", 2007)
Computational and experimental researches of the waste sandy-argillaceous mixture are presented in the article. The criterion of mixture destruction is got. The obtained results will allow to specify variable mechanical characteristics of moulding in a clod.
Keywords: формовочная смесь; отливки; решетки-грохоты; критерий разрушения; инерционная выбивная машина; вибровозбудители